Strategi metafizik: kesinambungan penerokaan domain strategi utama pembelajaran bahasa - Kamarul Shukri Mat Teh,; Mohamed Amin Embi,; Nik Mohd Rahimi Nik Yusoff,; Zamri Mahamod, (Penerbitan UKM, 2009)
The existence of the distinct typologies suggests the lack of a consensus for describing inventories and taxonomies of language learning strategies (LLS). There is no doubt that some arguments about present taxonomies still persist among researchers and some domains did not discover yet. This paper describes a preliminary study designed to explore and develop metaphysic strategy as a new subcategory in the classification systems of LLS. Based on an extensive literature review, items in the metaphysic subcategory questionnaire were developed. The internal consistency reliability as measured by Cronbach’s Alpha for the metaphysic strategy was 0.805. A total of 460 students from 13 Religious Secondary Schools in Terengganu participated in this study. The results showed that the metaphysic strategies were the next most frequently used after compensation strategies. The results also indicate that metaphysic strategies were among the most frequently used based on language proficiency and motivation level. The findings have contributed to providing a well-defined framework for further studies on metaphysic strategies and on factors affecting the choice of LLS